2019
DOI: 10.1080/14686996.2019.1659090
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion luminescence and favorable temperature sensing performance of eulytite-type Sr3Y(PO4)3:Yb3+/Ln3+ phosphors (Ln=Ho, Er, Tm)

Abstract: Phase-pure eulytite-type Sr3Y0.88(PO4)3:0.10Yb3+,0.02Ln3+ upconversion (UC) phosphors (Ln = Ho, Er, Tm) were synthesized via gel-combustion and subsequent calcination at 1250°C. Their UC luminescence, temperature-dependent fluorescence intensity ratio of thermally and/or non-thermally coupled energy levels, and performance of optical temperature sensing were systematically investigated. The phosphors typically exhibit green, orange-red and blue luminescence under 978 nm NIR laser excitation for Ln = Er, Ho and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(19 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…It is also seen from Figure A that the green band well splits into four sharp peaks centered at ~ 524, 540, 551 and 568 nm, respectively, which indicates that the 2 H 11/2 and 4 S 3/2 energy levels of Er 3+ are subjected to substantial splitting by the dodecahedral coordination environment in Li 6 CaLa 2 Nb 2 O 12 . Such a phenomenon was found for Gd 2 O 3 :Yb/Er, Y 2 O 3 :Yb/Er, LiYF 4 :Yb/Er, and NaLu(WO 4 ) 2 :Yb/Er, but hardly for YbPO 4 :Er, YPO 4 :Yb/Er and Sr 3 Y(PO 4 ) 3 :Yb/Er orthophosphates, La 2 O 2 S:Yb/Er oxysulfide, and La 2 O 2 SO 4 :Yb/Er oxysulfate . In addition, the broad and diffuse red luminescence extending from ~ 640 to 700 nm (Figure A) was similarly observed for Ba 5 Gd 8 Zn 4 O 21 :Yb/Er UC phosphor in the ~ 640‐680 nm spectral region, which was ascribed to widening of the 4 F 9/2 energy level by electronic interactions and spin‐orbit coupling .…”
Section: Resultsmentioning
confidence: 96%
“…It is also seen from Figure A that the green band well splits into four sharp peaks centered at ~ 524, 540, 551 and 568 nm, respectively, which indicates that the 2 H 11/2 and 4 S 3/2 energy levels of Er 3+ are subjected to substantial splitting by the dodecahedral coordination environment in Li 6 CaLa 2 Nb 2 O 12 . Such a phenomenon was found for Gd 2 O 3 :Yb/Er, Y 2 O 3 :Yb/Er, LiYF 4 :Yb/Er, and NaLu(WO 4 ) 2 :Yb/Er, but hardly for YbPO 4 :Er, YPO 4 :Yb/Er and Sr 3 Y(PO 4 ) 3 :Yb/Er orthophosphates, La 2 O 2 S:Yb/Er oxysulfide, and La 2 O 2 SO 4 :Yb/Er oxysulfate . In addition, the broad and diffuse red luminescence extending from ~ 640 to 700 nm (Figure A) was similarly observed for Ba 5 Gd 8 Zn 4 O 21 :Yb/Er UC phosphor in the ~ 640‐680 nm spectral region, which was ascribed to widening of the 4 F 9/2 energy level by electronic interactions and spin‐orbit coupling .…”
Section: Resultsmentioning
confidence: 96%
“… Rare earths and materials Transition Temperature (K) Sensitivity (S) (K −1 ) × 10 −4 at temp. (K) References Ho 3+ –Yb 3+ : Gd 2 O 3 5 F 4 / 5 S 2 → 5 I 8 300–800 18.0 (580) (S R ) 13.0 (798) (S A ) 17 Ho 3+ –Yb 3+ : BaTiO 3 5 F 4 / 5 S 2 → 5 I 8 12–300 2.0 (300) (S R ) 45 Ho 3+ /Yb 3+ (Glass–ceramic) 5 F 2,3 / 3 K 8 , 5 F 1 / 5 G 6 → 5 I 8 303–643 and 1119 10.2 (1119) (S R ) 47 Ho 3+ /Yb 3+ : Sr 3 Y(PO 4 ) 3 5 I 4 / 5 F 5 → 5 I 8 298–573 4.6 (573) (S A ) 48 Tm 3+ /Yb 3+ : Sr 3 Y(PO 4 ) 3 3 F 2,3 / 1 G 4 → 3 H 6 298–573 15.3 (573) (S A ) 48 Nd 3+ (Glass–ceramic) 4 F 5/2 / ...…”
Section: Resultsmentioning
confidence: 99%
“…At the highest measurement temperature of 548 K (275°C), the intensity of 524, 520, 530 nm drops to 67.7%, 87.9%, and 58.6% of the initial value, respectively. While the 4 right after the temperature increased and the intensity loss of the emission is mostly due to enhanced nonradiative relaxation by intensified lattice vibration at a higher temperature [8,39]. At the highest measurement temperature of 548 K (275°C), the intensity of 543, 552, 656, and 670 nm drops to 17.1%, 14.4%, 28.8%, and 26.3% of the initial value, respectively.…”
Section: Fluorescence Intensity Ratio (Fir)-based Luminescent Thermometry Of Na(gdyber)(wo 4 )mentioning
confidence: 95%
“…This further indicated that the phosphor can be used for luminescence thermometry. The quality of optical thermometry can be quantified via absolute sensitivity (S A ) and relative sensitivity (S R ) and Figure 10b shows the results of S A /S R derived from the following equations [8,9]:…”
Section: Fluorescence Intensity Ratio (Fir)-based Luminescent Thermometry Of Na(gdyber)(wo 4 )mentioning
confidence: 99%
See 1 more Smart Citation